Antifibrillatory effect of tetrahydroberberine - Sun An-Yang; Li De-Xing (Acta Pharmacologica Sinica, 2016)
Electric stimulation and drug-induced ventricular fibrillation (VF), monophasic action potentials (MAP), and triggered activity were studied before and after administration of tetrahydroberberine (THB) in rabbits, rats or guinea pigs. At doses of 5, 10, and 20 mg.kg-1, i.v. THB increased the ventricular fibrillation threshold, and the BaCl2-induced VF was also prevented or terminated by THB in rabbits. Centrogenic VF induced by icv aconitine in rats was inhibited by pretreatment with THB in a dose-dependent manner, whereas VF induced by iv ouabain in guinea pig was inhibited to a lesser degree. For MAP, the duration at 90% repolarization (MAPD90) was prolonged remarkably, whereas the MAPD20, the MAP amplitude, and the maximal velocity of phase 0 were shortened or decreased slightly. The amplitudes of early afterdepolarization produced by cesium chloride (CsCl) were attenuated, while the cumulative threshold doses of CsCl for sustained ventricular tachycardia were elevated by THB. These results indicated that THB had an potent antifibrillatory effect, which might be attributed to its blockade of potassium, calcium, and sodium currents.